The Relationship Between State Policies for Competitive Foods and School Nutrition Practices in the United States - Merlo, Caitlin L. (Centers for Disease Control and Prevention, 2014)
INTRODUCTION: Most students in grades kindergarten through 12 have access to foods and beverages during the school day outside the federal school meal programs, which are called competitive foods. At the time of this study, competitive foods were subject to minimal federal nutrition standards, but states could implement additional standards. Our analysis examined the association between school nutrition practices and alignment of state policies with Institute of Medicine recommendations (IOM Standards). METHODS: For this analysis we used data from the Centers for Disease Control and Prevention’s (CDC’s) report, Competitive Foods and Beverages in US Schools: A State Policy Analysis and CDC’s 2010 School Health Profiles (Profiles) survey to examine descriptive associations between state policies for competitive foods and school nutrition practices. RESULTS: Access to chocolate candy, soda pop, sports drinks, and caffeinated foods or beverages was lower in schools in states with policies more closely aligned with IOM Standards. No association was found for access to fruits or nonfried vegetables. CONCLUSION: Schools in states with policies more closely aligned with the IOM Standards reported reduced access to less healthful competitive foods. Encouraging more schools to follow these standards will help create healthier school environments and may help promote healthy eating among US children.